Analisis Pengaruh Live Streaming, Hedonic Shopping Motivation, Price Discount terhadap Impulse Buying (Studi pada Generasi Z Pengguna Social Commerce Tiktok) - Riri Carissa (eCo-Buss, 2024)
TikTok is experiencing rapid growth because it enables users to enjoy content and shop simultaneously on a single platform. The platform's live streaming feature allows users, creators, and businesses to promote and sell products. Not only that, hedonic shopping motivation can increase consumers' desire to continue shopping. Impulse buying made by consumers are also usually motivated by sales promotions such as price discounts. This study attempts to analyze the influence of Live Streaming, Hedonic Shopping Motivation, and Price Discount on Impulse Buying. This study employs quantitative methods by analyzing the outcomes of respondent questionnaires delivered via Google Form. The study focuses on Generation Z individuals who have used the live streaming commerce app (TikTok Shop). Sampling utilized non-probability sampling with a purposive technique, gathering 200 respondents meeting specific criteria measured across 19 indicators using a Likert Scale. Data were analyzed using SPSS Version 26. The research employed data analysis methods such as instrument validation, testing classical assumptions, and conducting hypothesis testing through multiple linear regression. The findings indicate that Live Streaming, Hedonic Shopping Motivation, and Price Discount each have a positive and significant influence, both individually and collectively, on Impulse Buying, contributing to 86.4% of the variance, while the remaining variance is attributed to other factors.